2023
DOI: 10.26508/lsa.202201735
|View full text |Cite
|
Sign up to set email alerts
|

FBXO11 governs macrophage cell death and inflammation in response to bacterial toxins

Abstract: Staphylococcus aureuscauses severe infections such as pneumonia and sepsis depending on the pore-forming toxin Panton–Valentine leukocidin (PVL). PVL kills and induces inflammation in macrophages and other myeloid cells by interacting with the human cell surface receptor, complement 5a receptor 1 (C5aR1). C5aR1 expression is tighly regulated and may thus modulate PVL activity, although the mechanisms involved remain incompletely understood. Here, we used a genome-wide CRISPR/Cas9 screen and identified F-box pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…It is a suspension cell line and suitable for transfection or infection experiments. In 2023, Naderer et al conducted a FACS-based genome-wide CRISPR/Cas9 screen in the THP-1 cell line to explore the mechanism between Panton-Valentine leukocidin (PVL) and complement C5a receptor 1 (C5aR1) (107). FBXO11 was identified as the potential target in macrophages for inflammation.…”
Section: Macrophages-mediated Diseasesmentioning
confidence: 99%
“…It is a suspension cell line and suitable for transfection or infection experiments. In 2023, Naderer et al conducted a FACS-based genome-wide CRISPR/Cas9 screen in the THP-1 cell line to explore the mechanism between Panton-Valentine leukocidin (PVL) and complement C5a receptor 1 (C5aR1) (107). FBXO11 was identified as the potential target in macrophages for inflammation.…”
Section: Macrophages-mediated Diseasesmentioning
confidence: 99%
“…Another recently reported CRISPR screen for PVL by Jeon et al was conducted in differentiated macrophages [ 156 ]. Besides the known PVL receptor C5AR1 , FBXO11 (F-box protein 11) was also enriched in the screen.…”
Section: Factors Involved In Unique Pathwaysmentioning
confidence: 99%
“…Jeon et al found that FBXO11 -knockout cells exhibited reduced transcription of C5AR1 that could be restored by lipopolysaccharide (LPS) priming. FBXO11 was further demonstrated to regulate the inflammasome pathway and the expression of IL-1β through BCL6-dependent and BCL6-independent transcriptional regulations [ 156 ].…”
Section: Factors Involved In Unique Pathwaysmentioning
confidence: 99%